POLA PEMENUHAN HAK DAN KEWAJIBAN SUAMI ISTRI LONG DISTANCE RELATIONSHIP (LDR) - Zakiah, Reza Umami (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2020)
Ideally, a married couple lives together to carry out their respective duties and obligations. However, because the demands of work cause some of them must be far apart and live the life of Long Distance Relationship (LDR) as happened in Batujaya Village, Kec. Batujaya, Kab. Karawang. The problem that arises is how the pattern of fulfilling the rights and obligations of husband and wife in Batujaya Village, Kec. Batujaya, Kab. Karawang. How to communicate on LDR and how to overcome the difficulties that arise between the two. Through research using descriptive analysis method, the results of the study show that: (1) The pattern of fulfilling the rights and obligations of a husband and wife who are on a LDR at Batujaya Village, Kec. Batujaya, Kab. Karawang can be understood in three aspects, namely the Financial/material aspect is done by meeting in person/transferring money through Alfamart/ATM/POS. The biological aspect when far apart is by interacting by telephone, occupying with homework. Psychological aspects, namely by giving attention over the phone or when meeting by serving all their needs. (2) The way of LDR husband and wife communication via telephone, massage, whatsapp, and video call, but for those who do not use the telephone as a communication tool, the communication is carried out directly when meeting. (3) The way to overcome the difficulties that arise between the two is to maintain mutual trust, understanding, commitment, intensive communication, mutual attitude. The difficulties faced are financial, trust, communication, cooperation and sexual needs.